Radiographic Analysis Between Two Commonly Used Measurements for Hallux Valgus Interphalangeus. Issue 4 (16th October 2019) - Lever, Caroline; Millward, Graham; Mason, Lyndon; Molloy, Andrew
Category: Bunion Introduction/Purpose: There is an increasing recognition of the contribution of hallux valgus interphalangeus (HVI) to the total deformity seen in hallux vallux valgus. The most commonly assessed radiological parameter is the hallux interphalangeus angle (HIA). Our aim in this study was to assess the reliability of the difference in medial and lateral proximal phalanx wall length (delta PP) in the assessment of hallux valgus interphalangeus in both the pre-operative and post-operative radiographs compared with the HIA. Methods: All patients undergoing scarf osteotomy for hallux valgus correction at our institution over a nine-month period were included. 40 feet in 36 patients were evaluated. Standard AP weight bearing radiographs preoperative and at 6 weeks post-surgery were evaluated by 2 independent observers. The standard PACS angular measurement tools were used for all measurements. The HIA and delta PP were measured along with hallux valgus angle (HVA) and intermetatarsal angle (IMA). Delta PP was calculated as the medial side length of the medial proximal phalanx minus the lateral side length of the proximal phalanx. SPSS 21 was used for statistical evaluation. Two-way random single measure intra-class correlation coefficient (ICC) was calculated to assess the interobserver agreement. Results: 33 female and 3 male patients were assessed. The mean age was 58 years (range 26-80 years). 18 patients underwent an Akin osteotomy. Pre-operative mean HVA 33 degrees, IMA 15 degrees, HIA 4 degrees and delta PP 1.64 mm. Post-operative mean HVA 17 degrees, IMA 9 degrees, HIA 7 degrees and delta PP 1.03 mm. In the sub group that underwent an Akin osteotomy the HIA increased from 5.2 degrees to 8.8 degrees in contrast to the delta PP that reduced from 2.04 to 0.26 mm. Pre-operatively the inter observer agreement using ICC was HVA 0.74, IMA 0.82, HIA 0.65 and Delta PP 0.70. Postoperatively the interobserver agreement was HVA 0.71, IMA 0.55, HIA 0.57 and Delta PP 0.64. Conclusion: The delta PP was more reliable than the HIA, with an improved interclass agreement on both pre and post- operative radiographs. The mean post-operative HIA increased, this was also present in the group where an akin osteotomy had been performed. In contrast the delta PP reduced. We feel pronation of the toe may alter the radiographic measures for HVI assessment and affect the validity of the HIA measurements, however the delta PP reliability was less affected. Pre-operative radiographs had greater interobserver agreement across all measures than postoperative radiographs, which may reflect difficulties in determining the bony landmarks for measurement following surgery.